Caring for you is straining me! -Strain among the informal caregivers of the elderly attending Health Centres of a Coastal City in Karnataka - Jacob, Ankeeta Menona; Kundapur, Rashmi; Ramachandra, Kavya (Indian Journal of Community Health, 2019)
Background: Census 2011 estimated 104 million elderly in India. Unprecedented demand for informal caregivers of elderly has resulted in physical, emotional and economic difficulties called caregiver strain. Aim & Objective: To determine the association between levels of strain among informal caregivers and the dependency levels of the elderly. Material & Methods: A cross-sectional study during January -March 2018 was conducted in the health centres attached to field practice areas of a tertiary care hospital. Data collection was done using a pre-tested, semi-structured questionnaire after informed consent from elderly and informal caregivers meeting the inclusion criteria. Statistical Analysis used: Data was entered in MS Excel and analysed using SPSS version 20. Percentages and proportions of Activities of daily living (ADL) and informal caregiver strain of Modified Caregivers Strain Index (MSCI) and their scores were expressed in median and interquartile range. Spearman’s Rho was used to determine the association of ADL and MCSI scores. Results: 47.5% of informal caregivers experienced mild stress; 70 % of the 200 elderly were fully functional. Strain level of the informal caregivers showed a negative correlation (0.557) with the dependency level of the elderly. Conclusion: With increasing dependency level of elderly, informal caregiver strain should be assessed.